Financial health of enterprises introducing safeguard procedure based on bankruptcy models - Schönfeld, Jaroslav; Kuděj, Michal; Smrčka, Luboš (Journal of Business Economics and Management, 2018)
This paper is focused on the financial situation of enterprises introducing safeguard procedure (in other words moratorium) in the Czech Republic. The paper’s aim is to show if the enterprises asking for the safeguard procedure do have financial conditions for recovering and maintaining the going concern principle. The safeguard procedure should help the enterprise to solve their problematic situation because it protects them against creditors for the court approved time period. The safeguard procedure cannot be successful when the financial situation is extremely poor and therefore this paper analyses the enterprises’ financial situation   upon applying for safeguard. The situation is evaluated using bankruptcy models, such as Altman Z-Score, Kralicek Quick Test, IN 99 and IN05. The evaluation is conducted in different time moments, specifically one year, two years and three years before implementing the safeguard procedure. Results for the individual enterprises are summed up by basic descriptive statistics as mean, median, low and upper quartiles. The results show that the financial situation of most enterprises was very poor before introducing the safeguard procedure and it had deteriorated during the years before.